2006
DOI: 10.1038/sj.emboj.7601286
|View full text |Cite
|
Sign up to set email alerts
|

TRIF–GEFH1–RhoB pathway is involved in MHCII expression on dendritic cells that is critical for CD4 T-cell activation

Abstract: Dendritic cells (DC) play a central role in immune responses by presenting antigenic peptides to CD4+ T cells through MHCII molecules. Here, we demonstrate a TRIF-GEFH1-RhoB pathway is involved in MHCII surface expression on DC. We show the TRIF (TIR domain-containing adapter inducing IFNbeta)- but not the myeloid differentiation factor 88 (MyD88)-dependent pathway of lipopolysaccharide (LPS)-signaling in DC is crucial for the MHCII surface expression, followed by CD4+ T-cell activation. LPS increased the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…Since TLR4 can utilize the MyD88 and the TRIF pathways to deliver signaling, the finding that MyD88 deficiency did not abolish upregulation of CD80, CD86, CD40, and MHC II molecules suggests that TRIF participated in the modulation of DC maturation. This is in line with previous reports demonstrating that a MyD88-independent, but TRIF-dependent signaling pathway was responsible for the surface expression of MHC II and costimulatory molecules in LPS-activated DC (17,23). In the present study, we saw a higher expression of MHC II in MyD88 KO DC than in WT DC after BRD509(pSBRT7), BRD509, SBR, LPS, or Pam3CSK4 stimulation, suggesting that MyD88 signaling exerts an inhibitory effect on MHC II expression.…”
Section: Discussionsupporting
confidence: 82%
“…Since TLR4 can utilize the MyD88 and the TRIF pathways to deliver signaling, the finding that MyD88 deficiency did not abolish upregulation of CD80, CD86, CD40, and MHC II molecules suggests that TRIF participated in the modulation of DC maturation. This is in line with previous reports demonstrating that a MyD88-independent, but TRIF-dependent signaling pathway was responsible for the surface expression of MHC II and costimulatory molecules in LPS-activated DC (17,23). In the present study, we saw a higher expression of MHC II in MyD88 KO DC than in WT DC after BRD509(pSBRT7), BRD509, SBR, LPS, or Pam3CSK4 stimulation, suggesting that MyD88 signaling exerts an inhibitory effect on MHC II expression.…”
Section: Discussionsupporting
confidence: 82%
“…administration of live or heat-killed E. coli in mice results in apoptosis of dendritic cells, and this process is mediated by TLR4 via a TRIF-dependent pathway and is independent of MyD88 (De Trez et al, 2005). Recently, a TRIF-specific and MyD88-independent pathway for TLR4 has been identified that provides a molecular mechanism relating how LPS induces major histocompatability class II expression during dendritic cell maturation (Kamon et al, 2006). It remains to be determined whether LPSmediated suppression of NRs and DMEs in the liver is controlled by a TRIF-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulated cells were fixed in 4% paraformaldehyde for 20 min, permeabilized with Perm/Wash solution (BD Biosciences Cytofix/Cytoperm kit), and incubated with rabbit antip65 (1:50) for 1 h. After washing, the cells were incubated with anti-rabbit Alexa Fluor 488-conjugated secondary Ab (1:200) and Hoechst 33342 nuclear stain (1:10,000) for 1 h. Cells were then observed by confocal microscopy (22).…”
Section: Confocal Microscopymentioning
confidence: 99%